Design of Sliding Mode Variable Structure Control System for the 3-RPS Parallel Mechanism - Chen Jianwei; Zhang Rongxing; Zhu Dachang; Zhu Chengwei (Jixie chuandong)
Because the conventional controller for parallel mechanism has low trajectory tracking precision,the sliding mode variable structure controller（ SMC） is designed based on the dynamics equation of 3-RPS parallel mechanism and proportional switching control law. Firstly,the Matlab / Sim Mechanics analysis model of 3- RPS parallel mechanism is established,the Jacobian matrix of 3- RPS parallel manipulator is solved by using the micro- displacement method and the optimal size parameters of the mechanism are determined by workspace analysis,which are the theoretical reference values for control system. Secondly,the SMC controller is established,the stability of SMC controller is proved by using the Lyapunov function. At last,the Matlab / Simulink block diagrams of PID controller and SMC controller are respectively established,the effects of PID controller with SMC controller are compared and analyzed,the results show that the trajectory tracking precision of SMC controller is higher than the PID controller,and the SMC controller has smaller steady- state error,faster response speed and better robustness,and the effectiveness of the SMC control is verified.